Designing a Financing Model for Small and Medium-Sized Enterprises in Iran to Improve Productivity Management - Sheida Orafaye Jamshidi; فرهاد رهبر; Ahmad Shabani; Karim Esgandari (مدیریت بهره وری)
Financing is one of the important issues that every industry faces in some way. Therefore, in order to maximize the wealth of shareholders, one of the decisions of the managers of small and medium sized industrial units is the decisions related to financing. Hence, the purpose of this research was to design a financing model for small and medium sized industries in Iran in order to improve productivity management. Since this research had a qualitative approach, the grounded theory method was used as a research method. The data was collected through in-depth and open interviews with 20 academic and industry experts, which was then coded and validated. The extracted codes included 411 concepts (open codes) and 20 main categories. Based on the systematic approach of foundational data theory, the identified codes were classified into six categories, including " central phenomenon, causal conditions, background conditions, intervening conditions, strategies and consequences". The results obtained from the interviews show that the central phenomenon of "financing" includes "drafting of financial plans during the financing process", "financial monitoring and evaluation during the financing process" and the categories of "development of operational activities", "developments of company's finances" and "company's environmental causes" as causal conditions have an effect on the categories of the central phenomenon. The foundational categories as necessary background conditions for the realization of financing in small and medium sized industries include: "financial accounting standards", "standardized financial statements", "company’s financial affairs management", "financing institutions", and "company's general management". Meanwhile, some categories act as interfering conditions in realizing financing in small and medium sized industries including: "macro environmental interventions", "internal company interventions" and "prerequisites for realizing financing" which are both background and intervention conditions. They can influence the presented strategies. These strategies include: "corporate discipline", "analysis and monitoring of the prevailing situation in the company", "actions and classification of matters for financing" and "using auxiliary levers" which are the necessary strategies in the implementation of financing in small and medium sized industries. If the central phenomenon is realized, the categories of "business excellence", organization of financial flows" and "economic development" can be expected as the resulting consequences.